The Impact of Infection Prevention Bundles on Neurosurgical Outcomes and Healthcare Costs: A Systematic Review - Putra, Fajar Faisal; Akhmad Imron; Muhammad Adam Pribadi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Post-operative infections represent a significant challenge in neurosurgery, leading to increased morbidity, mortality, and healthcare costs. The implementation of infection prevention bundles, which encompass a set of evidence-based practices, has emerged as a potential solution to mitigate these adverse outcomes. This systematic review aims to evaluate the effectiveness of infection prevention bundles in improving neurosurgical outcomes and reducing healthcare costs. Methods: A comprehensive search of electronic databases (PubMed, Scopus, Web of Science) was conducted to identify studies published between 2010 and 2023 that evaluated the impact of infection prevention bundles on neurosurgical outcomes and healthcare costs. The search strategy included keywords such as "neurosurgery," "infection prevention," "surgical site infection," "bundle," "outcomes," and "healthcare costs." Studies were included if they reported on at least one clinical outcome (e.g., surgical site infection rates, mortality, length of stay) and/or healthcare costs. Data extraction and quality assessment were performed independently by two reviewers. Results: The search yielded 45 studies that met the inclusion criteria. The studies encompassed a variety of neurosurgical procedures, including craniotomies, spinal surgeries, and deep brain stimulation. The infection prevention bundles implemented varied across studies but commonly included preoperative antibiotic prophylaxis, skin antisepsis, and intraoperative measures. The pooled analysis demonstrated a significant reduction in surgical site infection rates and length of stay associated with the use of infection prevention bundles. Moreover, several studies reported cost savings, primarily attributed to reduced complications and shorter hospital stays. Conclusion: The evidence suggests that infection prevention bundles are effective in improving neurosurgical outcomes and reducing healthcare costs. The implementation of these bundles should be considered a standard of care in neurosurgery to enhance patient safety and optimize resource utilization. Keywords: Neurosurgery, infection prevention, surgical site infection, healthcare costs, systematic review.